Security enhancements of the LTE-based vehicle communication networks - Prajapati Dipesh Bhikhabhai (2017)
The increasing demand for improving safety on roads and optimizing road traffic has brought a wide interest on vehicle to vehicle communication. LTE-based vehicle to vehicle (V2V) communications have been envisioned as a new key feature for short range wireless communications in the LTE and LTE – Advanced based networks. A 3GPP standard (Release 12) architecture has been recently defined to incorporate Proximity Services (ProSe) in the LTE core network. In this dissertation, a V2V system has been proposed using the LTE-Direct technology for finding out the vehicles which are available in the proximity. The system includes the feature of double authentication as the communicating vehicles are first registered with the LTE system through the EPS-AKA procedure and then they are again authenticated through the technique which includes the combination of Elliptical Curve Diffie Hellman key exchange (ECDH) protocol and Hybrid Message Authentication Protocol (HMAC). The direct message flowing between two vehicles are integrity protected through the HMAC.